Biogenic ethylene promotes seedling emergence from the sediment seed bank in an ephemeral tropical rock pool habitat - Cross, A.; Cawthray, G.; Merritt, D.; Tuner, S.; Renton, M.; Dixon, Kingsley (Springer, 2014)
Background and aims: Ethylene has been increasingly implicated as a regulatory mechanism in plant germination, growth, and development, and is produced from the sediments of freshwater habitats. In this paper, we analyse the production and origin of ethylene from ephemeral freshwater rock pool sediments, and explore the role of ethylene in regulating seedling emergence from the seed bank. Methods: The production of ethylene from rock pool sediments subjected to variable moisture content and antibiotic treatments was assessed through gas chromatography, and the role of ethylene in regulating seedling emergence was determined by seedling emergence assays and seed germination experiments. Results: Biogenic ethylene production from rock pool sediments occurred rapidly (3–6 h) following inundation, with the majority of seedling emergence occurring between 36 and 72 h. Inoculation of sediments with streptomycin and amphotericin B resulted in significantly reduced ethylene production (up to 60 % and 84 % respectively), and completely inhibited seedling emergence. Additionally, the exposure of dormant seeds to ethylene resulted in significantly increased seed germination percentage in five out of six rock pool species. Conclusions: Biogenic ethylene production may play an important role in regulating seed dormancy and the timing of seedling emergence from the sediment seed bank following inundation events in rock pools and other freshwater aquatic communities.